Recent advances in biochar engineering for soil contaminated with complex chemical mixtures: remediation strategies and future perspectives - Anae, Jerry; Ahmad, Nafees; Kumar, Vinod; Thakur, Vijay Kumar; Gutierrez, Tony; Yang, Xiao Jin; Cai, Chao; Yang, Zhugen; Coulon, Frederic (Elsevier, 2020)
Heavy metal/metalloids (HMs) and polycyclic aromatic hydrocarbons (PAHs) in soil have caused serious environmental problems, compromised agriculture quality, and have detrimental effects on all forms of life including humans. There is a need to develop appropriate and effective remediation methods to resolve combined contaminated problems. Although conventional technologies exist to tackle contaminated soils, application of biochar as an effective renewable adsorbent for enhanced bioremediation is considered by many scientific researchers as a promising strategy to mitigate HM/PAH co-contaminated soils. This review aims to: (i) provide an overview of biochar preparation and its application, and (ii) critically discuss and examine the prospects of (bio)engineered biochar for enhancing HMs/PAHs co-remediation efficacy by reducing their mobility and bioavailability. The adsorption effectiveness of a biochar largely depends on the type of biomass material, carbonisation method and pyrolysis conditions. Biochar induced soil immobilise and remove metal ions via various mechanisms including electrostatic attractions, ion exchange, complexation and precipitation. PAHs remediation mechanisms are achieved via pore filling, hydrophobic effect, electrostatic attraction, hydrogen bond and partitioning. During last decade, biochar engineering (modification) via biological and chemical approaches to enhance contaminant removal efficiency has garnered greater interests. Hence, the development and application of (bio)engineered biochars in risk management, contaminant management associated with HM/PAH co-contaminated soil. In terms of (bio)engineered biochar, we review the prospects of amalgamating biochar with hydrogel, digestate and bioaugmentation to produce biochar composites.
Keywords: Bioaugmentation; Digestate; Hydrogel; Biochar (Bio)engineering; Contaminated soil